Sensitivity analysis of geometrical parameters to study haemodynamics and thrombus formation in the left atrial appendage. (12th June 2018) - García‐Isla, Guadalupe; Olivares, Andy Luis; Silva, Etelvino; Nuñez‐Garcia, Marta; Butakoff, Constantine; Sanchez‐Quintana, Damian; G. Morales, Hernán; Freixa, Xavier; Noailly, Jérôme; De Potter, Tom; Camara, Oscar
Abstract: The left atrial appendage (LAA) is a complex and heterogeneous protruding structure of the left atrium (LA). In atrial fibrillation patients, it is the location where 90% of the thrombi are formed. However, the role of the LAA in thrombus formation is not fully known yet. The main goal of this work is to perform a sensitivity analysis to identify the most relevant LA and LAA morphological parameters in atrial blood flow dynamics. Simulations were run on synthetic ellipsoidal left atria models where different parameters were individually studied: pulmonary veins and mitral valve dimensions; LAA shape; and LA volume. Our computational analysis confirmed the relation between large LAA ostia, low blood flow velocities and thrombus formation. Additionally, we found that pulmonary vein configuration exerted a critical influence on LAA blood flow patterns. These findings contribute to a better understanding of the LAA and to support clinical decisions for atrial fibrillation patients. Abstract : The left atrial appendage (LAA) is a complex and heterogeneous protruding structure of the left atrium (LA). The role of the LAA in thrombus formation is not fully known yet. The main goal of this work is to identify the most relevant LA and LAA morphological parameters (pulmonary veins and mitral valve dimensions; LAA shape; and LA volume) in atrial blood flow dynamics. Our numerical analysis confirmed the relation between large LAA ostia, low blood flow velocities and thrombus formation.